Does leadership matter in managing the village-owned enterprise? - Digdowiseiso1Kumba; Eko Sugiyanto, Heru Dian Setiawan,; ., Suharyono (Opción, 2020)
The establishment of the village-owned enterprise (Badan Usaha Milik Desa – BUMDes), as stipulated in Law No. 6/2014 on Village, is an effort to increase economic growth, together with the equitable distribution of assets to the village community. It is expected to be a pillar of economic activity in the village that serves as an institution that remains committed to village characteristics. However, the existence of BUMDes has not fully produced satisfactory results in terms of continuation of the programs and profitability. Therefore, this qualitative study aims to determine the factors that influence the village head’s leadership. Using Northouse’s (2013) concept, this study finds that both task and relationship behaviour are very important factors to achieve success in managing BUMDes in Indonesia.